2011
DOI: 10.1111/j.1538-7836.2010.04069.x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis risk and survival in cancer patients with elevated C‐reactive protein

Abstract: Summary. Background: The incidence of venous thromboembolism (VTE) is increased among cancer patients. Objective: We assessed serum levels of C-reactive protein (CRP) in order to study their prognostic significance for VTE and survival in the prospective observational Cancer and Thrombosis Study (CATS). Patients and methods: This study includes patients with recently diagnosed cancer or progression of disease after remission. Occurrence of VTE and information on the patientsÕ anti-cancer-treatment are recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 35 publications
1
45
2
1
Order By: Relevance
“…Although leukocyte count is also a risk factor for VTE occurrence in our cohort, its inclusion in the multivariable model did not diminish the association of albumin level and VTE occurrence. In a previous investigation in a subset of solid tumor patients of the CATS cohort, Kanz et al showed that the VTE risk increased by 20% (HR 1.2, 95% CI 1.0-3.8, p 5 .037) per double increase in CRP levels [18]. We substituted leukocyte counts for CRP levels in the sensitivity analysis of this investigation and obtained similar results.…”
Section: Discussionsupporting
confidence: 68%
“…Although leukocyte count is also a risk factor for VTE occurrence in our cohort, its inclusion in the multivariable model did not diminish the association of albumin level and VTE occurrence. In a previous investigation in a subset of solid tumor patients of the CATS cohort, Kanz et al showed that the VTE risk increased by 20% (HR 1.2, 95% CI 1.0-3.8, p 5 .037) per double increase in CRP levels [18]. We substituted leukocyte counts for CRP levels in the sensitivity analysis of this investigation and obtained similar results.…”
Section: Discussionsupporting
confidence: 68%
“…Moreover, IL-6 might not only be induced by chemotherapy, but also mediate therapy resistance, which could add to the worse prognosis of patients with high circulating IL-6 levels [38]. Interestingly, in a former study by our group, enhanced levels of C-reactive protein (CRP), an acute-phase protein known to be induced strongly by IL-6, indicated a worse prognosis of cancer patients not associated with VTE frequency [13]. These observations suggest that a direct tumour-promoting effect might underlie the negative prognostic impact of IL-6.…”
Section: Discussionmentioning
confidence: 88%
“…Many risk factors related to patient characteristics, tumour types and treatment influence the development of VTE in cancer patients [6]. A number of biomarkers of haemostasis and inflammatory markers have been found to play the role of risk factors of VTE in patients with cancer [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…As thrombosis is one of the serious complications in cancer patients, the dual actions support that as an antitumor agent, ATIQCTPC is able to prevent cancer patients from suffering from thrombosis. 32,33 As mentioned earlier, the serum concentrations of TNF-α and IL-8 of the S180 mice orally treated with 0.01 μmol/kg/day of ATIQCTPC are significantly lower than those of the S180 mice orally treated with NS. The findings of ATIQCTPC effectively downregulating serum TNF-α and IL-8 of S180 mice lead to a hypothesis that via decreasing serum TNF-α and IL-8, ATIQCTPC slows tumor growth of S180 mice.…”
Section: Discussionmentioning
confidence: 91%